PARIWISATA BUDAYA: PIKAMA MAANO KAMPO DALAM STRATEGI PENGEMBANGAN WISATA DESA WASUEMBA KECAMATAN WABULA - Herianto, Herianto; Sanusi, Sanusi (Jurnal Daya Saing, 2024)
This study aims to analyze the cultural tourism strategy of Pikama Maano Kampo in developing cultural tourism, as well as the supporting and inhibiting factors in Wasuemba Village using SWOT analysis. The type of research used in this study is qualitative research. The research location is in Wasuemba Village, Wabula District, and the sample was selected using purposive sampling. The internal supporting factors include the uniqueness of the Pikama Maano Kampo culture, traditional dances and martial arts in the Pikama Maano Kampo ceremony, the friendliness of the Wasuemba villagers towards tourists, the Happy Nice festival, and the Lahonduru tourist attraction. On the other hand, internal inhibiting factors include the lack of restaurants, homestays, and hotels, the absence of financial transaction facilities (ATMs), and insufficient promotion. External supporting factors include the support of village and district government policies in developing cultural tourism. The external inhibiting factors are the lack of public transportation to the tourist sites, the difficulty in community acceptance of different cultures from tourists, and low community participation. The quantitative SWOT analysis shows a position in Quadrant I with the axis points of (X 0.44) and (Y 0.08).